Meningkatkan Kemampuan Kognitif Anak Melalui Media Magic Square - Herayati, Trisni; budiarti, Tri rahayu; Indrawati, Yulia; setyorini, Wirastri; Purwaningsih, Sri Juani (Jurnal Pendidikan Indonesia, 2022)
The aims of this study were to improve student’s cognitive abilities of Fawwaz Kids School Kindergarden at A group in doing their activities in the class by using Magic Squere as the media. Fawwaz Kids School Kindergarden has many kinds of media that could support sudents’ cognitive aspects development, one of them through magic square which was able to increase students’ cognitive such as critical thinking, recognize and present the things around them. Based on the interviews, the teachers told that the student’s had not use or play this media yet. Therefore, by this media the student’s was expected to practise their ability to solve the problem, complete the task, and get the chance to play a new game to improve their study. The trial used by 10 students. The result of this study showed student’s interest in playing magic square media which were 88,89% students had critical thinking, 77,78 % students recognized and presented the things around them